RESEÑA de: MARTÍNEZ-BUJÁN PÉREZ, Carlos. "Derecho penal económico. Parte General". Ed. Tirant lo Blanch, Valencia, 1998. 246 pp. - Gracia Martín, Luis (Revista de Derecho Penal y Criminología, 2019)
-